Peircean Semiotics Analysis of Emojis and Their Meanings in Comments on the @girls Instagram Account - Suryadi, Fidela Shaumi; Hkikmat, Mahi M.; Sakinah, R. Myrna Nur (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Emoji interpretation has become an important issue in digital communication because emojis do not always carry fixed meanings and are often understood through their relationship with verbal text and interactional context. In semiotic studies, emojis can be examined as signs that contribute to meaning-making in online discourse. This article aims to analyze how emojis function as signs and how their meanings are constructed in the comment section of the @girls Instagram account by applying Charles Sanders Peirce’s triadic theory. This research employed a descriptive qualitative design. The data were taken from one selected post uploaded on the @girls Instagram account and consisted of nine comments containing emojis. The data were collected through observation and screenshots, then analyzed using Peirce’s triadic framework, which includes representamen, object, and interpretant. The findings show that emojis in the selected comments function as meaningful signs rather than merely decorative elements. The analysis revealed four meaning categories: agreement (1 comment), sadness (2 comments), humor (2 comments), and alternative viewpoints (4 comments). These meanings were shaped by the relationship between the emojis, the accompanying verbal text, and the context of the post. In conclusion, emojis play an important role in shaping meaning in Instagram comments. This study implies that emoji interpretation should be understood as part of visual-verbal meaning-making in digital communication and semiotic analysis.